(untitled) (Altre Modernità, 2021)
We analyse the representation of the end of ETA’s terrorism in the contemporary self-fiction theatre. Therefore we study the importance of the physical walls considering the symbolical values they represent and the social, mental and emotional barriers that lead the characters to repeat political struggles, generation after generation. The vision of reconciliation and forgiveness may be dark if it becomes possible only when those walls and their cultural background are knocked down, or it can be bright if it is considered as an emancipation from that background.